Effect of low-temperature hydrothermal treatment of HZSM-5 extrudates on the production of deeply-deoxygenated bio-oil via ex-situ catalytic fast pyrolysis of biomass. (15th September 2022) - Promsampao, Nuttapan; Chollacoop, Nuwong; Pattiya, Adisak
Graphical abstract: Highlights: Catalytic bio-oils appeared in 3 phases – heavy, light and aqueous fractions. Mass and energy yields of bio-oils were enhanced by hydrothermal treatment. Maximum organic liquid yield of 11.4 wt% with 3 wt% oxygen content was achieved. The liquid contained 6.7 wt% heavy oil and 4.7 wt% light oil. Irreversible catalyst deactivation was observed when applying high B/C ratio. Abstract: Catalytic fast pyrolysis (CFP) of biomass has high potential for producing deoxygenated bio-oil in one single process. HZSM-5 is a widely used catalyst for this purpose and various parameters have already been extensively investigated on this catalytic material. Limited studies were performed on the effect of low-temperature hydrothermal treatment of the catalyst with none being applied in ex-situ CFP in a lab-scale pyrolysis unit. The current paper therefore reports the investigation of HZSM-5 characteristics and activities when hydrothermally treated by steam at 550 °C for 5 h. The treatment modified the catalyst in a positive way that can increase 30% of the non-aqueous catalytic bio-oil yield. A maximum organic liquid yield of 11.4 wt% was achieved with 6.7 wt% being heavy fraction and 4.7 wt% being light fraction. These heavy and light bio-oils had very low oxygen contents of 4.3 and 1.6 wt%, respectively. This is equivalent to 93% oxygen removal compared to its corresponding non-catalytic bio-oil. Based on the elemental, FTIR, and GC/MS analyses, the hydrothermal treatment slightly increased the bio-oil oxygen content. Characterization of the catalysts reveal irreversible catalyst deactivation by dealumination. The severity of the deactivation increased continuously with higher amount of biomass being fed to the process. However, the catalyst deoxygenation ability was still acceptable for producing partially-deoxygenated bio-oil even after applying the biomass-to-catalyst ratio of 20.5.